Isotopically labeled boldenone as a better marker of derivatization efficiency for improved quality control in anti‐doping analysis. Issue 2 (26th December 2018) - Sobolevsky, Tim; Kucherova, Yulia; Ahrens, Brian
Abstract: At present, anti‐doping laboratories use androsterone, a major urinary steroid metabolite, to evaluate completeness of the derivatization step. This is typically done by calculating the ratio of mono‐trimethylsilyl (TMS) androsterone to the total mono‐ and di‐TMS androsterone. Certain samples may show an elevated percentage of mono‐TMS androsterone indicating a failed derivatization step. In such cases, the laboratory would have to repeat the analysis or perform other remedial actions to ensure that completeness of derivatization is achieved. We have noticed that a poorly derivatized positive control sample spiked with various target analytes has a disproportionally low abundance of the di‐TMS derivatives of boldenone and 18‐nor‐17β‐hydroxymethyl‐17α‐methylandrosta‐1, 4, 13‐trien‐3‐one (methandienone long‐term metabolite). A follow‐up investigation confirmed that 1, 4‐diene‐3‐one steroids are more likely to fail during the trimethylsilylation step. To better control derivatization efficiency, 13 C3 ‐boldenone (13C‐BLD) was incorporated into our routine procedure as an additional internal standard. Analysis of a large number of urine samples has shown that derivatization of 13C‐BLD could be grossly incomplete even in cases when mono‐TMS androsterone is well below 1%. In other words, one or both of boldenone and the long‐term metabolite of methandienone could remain undetected unless the laboratory has the means to recognize samples where derivatization of 1, 4‐diene‐3‐one steroids failed.